2017
DOI: 10.1002/elan.201700611
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Studies of Ethoxyquin and its Determination in Salmon Samples by Flow Injection Analysis with an Amperometric Dual Detector

Abstract: Ethoxyquin (EQ) is an antioxidant widely used in the food industry. Some concerns for human health have been reported since its utilization in animal feed may lead to residues in human food such as salmon samples. This work aimed to investigate the electrochemical behavior of EQ and its major oxidation products namely a dimer of EQ (EQDM) and ethoxyquin quinone imine (EQI) by cyclic voltammetry (CV) at a carbon screen printed electrode (cSPE). The stability of these products and their reactivity against glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…To investigate whether TIMS separation is also suitable for larger conjugates, the tripeptide GSH, which is relevant in phase II metabolism, was used in the following application of our developed online chipEC-TIMS-ToF-HRMS method. With a monoisotopic mass of 307 Da, GSH is almost twice as heavy as NAC (163 Da) and has already been described in its conjugate formations with many oxidatively activated drugs. Based on the previously shown reactions for EQI and NAC, a possible pathway for EQI and GSH is shown in Figure a, route 3, which was already postulated by Vandeput et al in 2018 . Since the TIMS separation depends on the charge, size, and shape of the investigated compound, the GSH conjugate isomers were expected to behave differently from the previously described conjugates.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…To investigate whether TIMS separation is also suitable for larger conjugates, the tripeptide GSH, which is relevant in phase II metabolism, was used in the following application of our developed online chipEC-TIMS-ToF-HRMS method. With a monoisotopic mass of 307 Da, GSH is almost twice as heavy as NAC (163 Da) and has already been described in its conjugate formations with many oxidatively activated drugs. Based on the previously shown reactions for EQI and NAC, a possible pathway for EQI and GSH is shown in Figure a, route 3, which was already postulated by Vandeput et al in 2018 . Since the TIMS separation depends on the charge, size, and shape of the investigated compound, the GSH conjugate isomers were expected to behave differently from the previously described conjugates.…”
Section: Resultsmentioning
confidence: 77%
“…The formal loss of 2 H suggests that this is an oxidation product of the formed conjugate TQ-NAC with m/z 351.1373, called EQI-NAC. This behavior has already been described by Vandeput et al 9 A possible explanation for this oxidized form is the atmospheric oxygen causing further oxidation before detection by TIMS-ToF-HRMS. Since the signal of EQI-NAC is more intense and more accessible for further experiments, the focus is placed on the EQI-NAC conjugate.…”
Section: Electrochemical Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the years 2018-19, nine new methods using FIA-SPE systems were developed for the determination of analytes such as isoniazid, [60] arsenic, [61] salmonella bacteria, [62] o-diphenol and its derivatives, [63] ethoxyquin, [64] glucose, [65] naproxen, [66] three tumor biomarkers, [67] acetaminophen, [68] and tryptophan and pyridoxine simultaneously. [69] Oliveira et al [62] reported a simple, low-cost, and fully disposable microfluidic FIA device for ultrasensitive Salmonella bacteria detection.…”
Section: Spes Coupled To Fia Systemsmentioning
confidence: 99%
“…Interestingly, coulometric detector is rarely used as detector for simple flow injection systems. However, flow injection methods are of particular interest for quality control as they allow to increase the amount of analyzed samples . Such electronic tongue was recently used for rapid determination of antioxidant capacity of lettuce, increasing the amount of analysis to 60 samples per hour .To the best of our knowledge, flow injection method based on coulometric array detection has never been applied for analysis of capsaicinoids in chili extracts.…”
Section: Introductionmentioning
confidence: 99%